2021
DOI: 10.1128/mra.00496-21
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Surveillance of SARS-CoV-2 Viruses Collected during the Ending Phase of the First Wave of the COVID-19 Pandemic in Bangladesh

Abstract: Mutations, deletions, and the emergence of new variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may pose a serious health threat. Here, we report the genome sequences of SARS-CoV-2 viruses that were collected from SARS-CoV-2-infected patients during the end phase of the first wave of the COVID-19 pandemic in Dhaka, Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Our finding is supported by reports of high anti-S protein IgG on the day of positive swab among unvaccinated COVID-19 patients in the United Kingdom having confirmed SARS-CoV-2 re-infection [39]. On this basis, we conclude that the patients with the delta variant likely have pre-existing antibodies from either the first Bangladesh pandemic wave in April to June 2020 [29][30][31][32] or the second Bangladesh pandemic wave in March 2021, which were predominantly of the SARS CoV-2 alpha or beta variants [25][26][27][28]40].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding is supported by reports of high anti-S protein IgG on the day of positive swab among unvaccinated COVID-19 patients in the United Kingdom having confirmed SARS-CoV-2 re-infection [39]. On this basis, we conclude that the patients with the delta variant likely have pre-existing antibodies from either the first Bangladesh pandemic wave in April to June 2020 [29][30][31][32] or the second Bangladesh pandemic wave in March 2021, which were predominantly of the SARS CoV-2 alpha or beta variants [25][26][27][28]40].…”
Section: Discussionsupporting
confidence: 88%
“…The extensive genomic surveillance of SARS CoV-2 viral isolates in Bangladesh throughout the pandemic is motivated by the urgency to identify the next strains of SARS CoV-2 carrying S-protein mutations or other genetic changes [25][26][27][28][29][30][31][32][33][34]. In the first and second pandemic waves in Bangladesh, the alpha and beta variants of the B.1.1.7 and B.1.351 lineages were associated with an Ro of approximately 1.2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…In case of first wave, several SARS-CoV-2 variants tried to increase their transmissibility through certain spike protein mutations. For example, mutations such as S:P681R/H were associated with enhanced transmission [ 79 ]. It has been reported that variants with S:D614G and S:Q675H mutations are relatively less infectious [ 80 ].…”
Section: Discussionmentioning
confidence: 99%